Nitrate uptake by foraminifera and use in conjunction with endobionts under anoxic conditions. (12th October 2014) - Nomaki, Hidetaka; Chikaraishi, Yoshito; Tsuchiya, Masashi; Toyofuku, Takashi; Ohkouchi, Naohiko; Uematsu, Katsuyuki; Tame, Akihiro; Kitazato, Hiroshi
Abstract : Among eukaryotes, some benthic foraminiferal species have been reported to be capable of nitrate respiration, although little is known about their denitrification processes. In this study, we incubated the shallow‐water benthic foraminifer Ammonia beccarii with isotopically labeled sodium nitrate (−73‰, 0‰, or +73‰) under oxic or anoxic conditions to investigate how nitrate is used in foraminiferal cells and whether those signatures remain in amino acids. The δ 15 N values of amino acids from bulk cells incubated under anoxic conditions were correlated with those of nitrate in seawater and were enriched in 15 N by up to ∼ 50‰ compared to the isotopic compositions in seawater. There was no such relationship or enrichment in the cases of organic matter in the calcite tests under oxic or anoxic conditions or bulk cells under oxic conditions, suggesting that benthic foraminifera take up ambient nitrate under anoxic conditions and use it for denitrification; the remaining 15 N‐enriched intracellular nitrate pool is used for amino acid synthesis, probably by endosymbiotic microbes, as suggested by observation of the cellular ultrastructure. The degree of 15 N enrichment may depend on denitrification rates of the intracellular nitrate pool. Because the amino acids in the calcite test are synthesized by foraminifera, they were not enriched in 15 N, even under anoxic conditions. Thus, differences between amino acid δ 15 N of bulk foraminiferal cells and organic matter in tests may serve as a proxy for denitrification in foraminiferal cells and microbial amino acid synthesis under oxygen‐depleted conditions.